The Influence of Contceptual Understanding Procedures (CUPs) Learning Model with Bio-Quartet Cards on Secondary School Students Learning Interest and Outcomes on Energy Material - Ariesta, Putri; Susanti, R; Rahayu, Enni Suwarsi (FMIPA UNNES, 2019)
This study aimed to describe the influence of Conceptual Understanding Procedures (CUPs) learning model with the use of bio-quartet cards on the seventh grade students’ learning interest and outcomes on Energy material at SMP N 17 Tegal. The study employed Quasi Experimental; Nonrandomized Control Group Pretest and Posttest Design. Population of the study was all the seventh grade students from 8 classes in the academic year 2017/2018. The sample was taken by using purposive sampling technique, obtaining two classes as the subject of this study. VII G as the control group was taught using discovery learning model and VII H as the experimental group was given CUPs learning model with the use of bio-quartet cards. The result of this study showed N-gain of students’ learning outcomes of the experimental group was 0.33 and that of the control group was 0.24. Control group learning interest was stagnant, on the other hand, experimental group learning interest improved at 3% on “very interest” category. Students’ learning interest and outcomes of both groups were not significantly different. The correlation test results of the two variables clearly showed that students’ learning interest and outcomes do not relate significantly, both the experimental group and the control group.